Rice seed production and marketing practices in Nepal - Gautam, Devendra; Magar, Dinesh Babu Thapa; Gautam, Sudeep (Journal of Agriculture and Environment, 2018)
Production and marketing of rice seed involves diverse activities and actors in seed value chain. This study aims to investigate practices and pattern of rice seed production and marketing in Nepal employing survey of 270 seed producers and 240 seed dealers and retailers covering most of the Terai and market accessible hills. The finding showed that seed business activities are concentrated on later generation seeds produced by diverse actors but marketed mainly through seed dealers and retailers. The most popular varieties with highest seed sales are Radha-4, Sabitri and US 312 (hybrid) respectively. Seed dealers selling hybrids receive higher benefits due to their higher market margins. The major constraints faced by seed actors are low profit margins in seed marketing of domestic varieties as compared to exotic hybrids. Improving rice seed business requires strengthening seed production and marketing of domestically developed varieties through entrepreneurship development, networking and policy support.